The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2265.2006.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Kickboxing sport as a new cause of traumatic brain injury‐mediated hypopituitarism

Abstract: Present data clearly demonstrate for the first time that amateur kickboxing is a novel cause of hypopituitarism and kickboxers are at a risk for hypopituitarism especially isolated GH deficiency. Therefore, participants of the combative sports who were exposed to chronic repetitive head trauma need to be screened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 43 publications
(96 reference statements)
3
78
3
6
Order By: Relevance
“…It is interesting that only recently has research begun to examine the role of pituitary injury in TBI to functional outcome, even in concussion (Acerini et al, 2006;Kelestimur, 2005;Kelly et al, 2006;Tanriverdi et al, 2007). As shown by the Bayly et al (2005) and Viano et al (2005b) studies, the hypothalamic-pituitary axis is particularly vulnerable to physical strain in concussion.…”
Section: Confounding Factors That Must Be Considered In the Design Ofmentioning
confidence: 99%
“…It is interesting that only recently has research begun to examine the role of pituitary injury in TBI to functional outcome, even in concussion (Acerini et al, 2006;Kelestimur, 2005;Kelly et al, 2006;Tanriverdi et al, 2007). As shown by the Bayly et al (2005) and Viano et al (2005b) studies, the hypothalamic-pituitary axis is particularly vulnerable to physical strain in concussion.…”
Section: Confounding Factors That Must Be Considered In the Design Ofmentioning
confidence: 99%
“…19 Studies in kickboxers and retired boxers also have reported relatively high rates of hypopituitarism; in one report, isolated GH deficiency (GHD) was documented in 45% of subjects, and the severity of GHD correlated with the number of bouts and boxing career duration. [20][21][22][23] In another study by Bondanelli and colleagues, chronic hypopituitarism was observed in 37% of mTBI patients. 10 Given the high rate of repetitive head impact and recurrent concussion in professional football players, and the depression, poor QoL, and obesity that are relatively common among NFL retirees, we hypothesized that pituitary dysfunction could be a contributing factor to their poor physical and mental health status.…”
Section: Introductionmentioning
confidence: 99%
“…47 Small case series in boxing and kickboxing have shown a high rate of GHD, and one case report highlighted the association between repeat concussion in an adolescent athlete and subsequent anterior hypopituitarism. 15,19,[21][22][23]48 Quality of life, erectile dysfunction, metabolic syndrome, and obesity…”
Section: Previous Studies On Postconcussive Hypopituitarismmentioning
confidence: 99%
“…Makroadenomlar daha fazla oranda hipofizer yetmezliğe neden olurken (%30-60) nonfonksiyone mikroadenomların da (%42) BH eksikliğine neden olduğu gösterilmiştir [11]. Son dönemlerde yapılan çalışmalar sonucunda beyin hasarı (travmatik beyin hasarı, spora bağlı tekrarlaycı kafa travması ve subaraknoid kanaması) olan hastaların da hipofizer yetmezlik açısından değerlendirilmesi gerektiği ortaya çıkmıştır [12][13][14]. Özellikle şuur kaybı olan ve 24 saat hastanede kalan travmatik beyin hasarı olanlar travmadan 6-12 ay sonra hipofizer yetmezlik açısından değerlendirilmelidir [15].…”
Section: Erişkin Dönemde Başlayan Bh Eksikliğiunclassified